Revised safety evaluation of the food enzyme endo‐1,4‐β‐xylanase from the genetically modified Bacillus subtilis strain LMG S‐24584 produced by a modified process - EFSA Panel on Food Enzymes (FEZ); Holger Zorn; José Manuel Barat Baviera; Claudia Bolognesi; Francesco Catania; Gabriele Gadermaier; Ralf Greiner; Baltasar Mayo; Alicja Mortensen; Yrjö Henrik Roos; Marize L. M. Solano; Monika Sramkova; et al. (EFSA Journal)
Abstract The food enzyme endo‐1,4‐β‐xylanase (4‐β‐d‐xylan xylanohydrolase, EC 3.2.1.8) is produced with the genetically modified Bacillus subtilis strain LMG S‐24584 by Puratos NV. In a previous opinion, the Panel noted the presence of recombinant DNA in all food enzyme batches tested. As a follow‐up, the applicant changed the manufacturing process of the food enzyme and provided new data. The genetic modifications do not give rise to safety concerns and the production strain fulfils the requirements for the QPS approach to safety assessment. The food enzyme is free from viable cells of the production organism and its DNA. It is intended to be used in the processing of cereals and other grains for the production of baked products. Dietary exposure is estimated to be up to 0.010 mg TOS/kg body weight per day in European populations. As no concerns arising from the microbial source and its genetic modifications or from the manufacturing process have been identified, the Panel considered that toxicological tests were not needed for the assessment of this food enzyme. A search for the homology of the amino acid sequence of the food enzyme to known allergens was made and no match was found. The Panel considered that the risk of allergic reactions upon dietary exposure cannot be excluded, but the likelihood is low. Based on the data provided, the Panel concluded that this food enzyme does not give rise to safety concerns, under the intended conditions of use.